Legitimization as a rhetorical process in a regulatory agency: An examination of rhetoric from the US Council for Higher Education Accreditation. Issue 2 (2nd May 2017) - Berry, Alison
Abstract : Purpose: The purpose of this paper is to identify how the US Council for Higher Education Accreditation (CHEA) communicatively engaged in legitimization concerning accreditation. Design/methodology/approach: This study utilized the rhetorical analysis approach outlined by Hoffman and Ford (2010) to explore the accreditation-related texts from an online source created by CHEA, Information About Accreditation. Findings: The analysis identified three overarching approaches to include: isomorphism to address regulatory legitimacy, organizational identity management to address pragmatic legitimacy, and a dialogic approach to address normative legitimacy. This analysis also developed a new theoretical model for the rhetorical construction of legitimacy, "A Model for the Rhetorical Construction of Legitimacy, " that can be summarized as: organizations foster a type of legitimacy through a legitimizing strategy by demonstrating how the purpose of the legitimizing strategy is achieved by the implementation of the legitimizing strategy. Research limitations/implications: Limitations include that data were gathered only from online, web-based texts during a period in which the rhetorical situation was ongoing. Practical implications: This study expands research concerning the rhetorical approach to issues management in that it examines the way legitimacy is negotiated through the various rhetorical strategies of an organization. Additionally, information is offered about the rhetorical structure of texts when an organization seeks to legitimize certain ideas. Originality/value: This analysis developed a theoretical model for the rhetorical construction of legitimacy, "A Model for the Rhetorical Construction of Legitimacy, " that demonstrates important relationships between legitimizing strategies and types of legitimacy. Understanding these relationships may allow for a better interpretation of how legitimacy theory is represented within a communicative venture.